Does escitalopram reduce neurotoxicity in major depression?. (July 2015) - Halaris, Angelos; Myint, Aye-Mu; Savant, Vidushi; Meresh, Edwin; Lim, Edwin; Guillemin, Gilles; Hoppensteadt, Debra; Fareed, Jawed; Sinacore, James
Abstract: A pro-inflammatory state and a dysregulation in the tryptophan/kynurenine pathway have been documented in depression. This study examined whether treatment with the SSRI, escitalopram (ESC), could suppress inflammation and favorably shift metabolites of the kynurenine pathway in patients with major depressive disorder (MDD) within the utilized treatment period. Twenty seven healthy control subjects were included for comparison. Thirty patients were enrolled after completing baseline assessments. They received a 12-week ESC monotherapy. Twenty subjects were completers. Clinical assessments were carried out at each visit using the HAM-D, HAM-A, CGI and BDI rating scales. Blood samples were collected at each assessment and stored until analyzed. Cytokines were analyzed with Randox multiplex assay and tryptophan and kynurenine metabolites were analyzed using HPLC/GCMS. Baseline plasma concentrations of hs CRP, TNFα, IL6 and MCP-1 were significantly higher in patients compared to healthy controls. IL10 trended toward an increase. Baseline plasma IL1β correlated significantly with IL1α, and IL4. Patients showed significant improvement in all outcome measures with a high remission rate. Significant correlations were obtained between specific symptoms and certain biomarkers at baseline but these correlations must be viewed as very preliminary. During ESC treatment concentrations of inflammatory biomarkers did not change except for TNFα that trended lower. Metabolites and ratios of the tryptophan/kynurenine pathway showed reductions of the neurotoxic metabolites, 3-hydroxykynurenine and quinolinic acid, 3-hydroxykynurenine/kynurenine, quinolinic acid/tryptophan, kynurenic acid/quinolinic acid and quinolinic acid/3-hydroxykynurenine. The results indicate that ESC may exert its antidepressant effect in part through inhibition of synthesis of certain neurotoxic kynurenine metabolites and possibly also through reduction of the inflammatory response, although there was no concordance in the time course of changes between antidepressant efficacy and reversal of the pro-inflammatory status. Highlights: Certain baseline inflammation biomarkers were elevated in MDD patients. Escitalopram induced a high remission rate but no change in inflammation biomarkers. Metabolites of the tryptophan/kynurenine pathway showed robust reductions of the neurotoxic metabolites. Significant correlations were obtained between symptoms and biomarkers at baseline.